Antibiotic Dispensing Practice by Medicine Sellers in Dhaka City-A Cross-Sectional Study - Nazrina, Sayeda; Rahman, Md Sayedur; Naznin, Rubiat (Community Based Medical Journal, 2021)
Dispensing antibiotics without prescription is a potential source of inappropriate use. Improvement of antibiotic use is very important in developing countries like Bangladesh. This cross-sectional observational study was conducted in Dhaka city, Bangladesh among 100 purposively selected medicine shops to observe antibiotic dispensing practices of medicine sellers on request for the treatment of nonspecific Upper Respiratory Tract Infection (URTI). Actual practice was assessed with simulated client visit (SCV) with 2 encounters in each medicine shops (a total of 200 encounters). Later self-stated practice was assessed through in-depth interviews with medicine sellers using a digital voice recorder. A total of 42 medicine sellers (42%) interviewed that they would have recommended antibiotics in response to a presentation of nonspecific URTI. In actual practice, antibiotics were dispensed in 108(54%) simulated visits. Total 5 drugs (tab ciprofloxacin, tab azithromycin, cap amoxicillin, cap cephradine, tab levofloxacin) was suggested by medicine sellers. Tab ciprofloxacin is the most preferable dispensed drug by medicine sellers in both actual and stated practices which were 73.15% (79/108 SCV) and 40.48 %( 17/42 medicine sellers) respectively. The most frequent question was "duration of disease" which was asked by medicine sellers in 76 %( 152/200) SCV. None of the medicine sellers asked about allergic history. Antibiotics were dispensed by medicine sellers in Dhaka city without prescriptions and appropriate indications. CBMJ 2020 January: Vol. 09 No. 01 P: 11-18